2022
DOI: 10.1080/07853890.2022.2108551
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based interventions for non-affective psychosis: a comprehensive systematic review and meta-analysis

Abstract: Aim Although mindfulness-based interventions (MBIs) are routinely used in clinical practice, a comprehensive synthesis of the effectiveness of MBIs for non-affective psychosis has yet to be conducted. The aim of the present review and meta-analysis was to investigate the effectiveness of MBIs including those with mindfulness as an active treatment component for alleviating symptoms of psychosis to inform future clinical practice. Methods A systematic review of studies p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Mindfulness for psychosis has been shown to have beneficial effects on positive psychotic symptoms, including voices (Jansen et al, 2020; Louise et al, 2018; Yip et al, 2022). However, due to a lack of dismantling studies in the field, the relative efficacy of different treatment components (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness for psychosis has been shown to have beneficial effects on positive psychotic symptoms, including voices (Jansen et al, 2020; Louise et al, 2018; Yip et al, 2022). However, due to a lack of dismantling studies in the field, the relative efficacy of different treatment components (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Studies have found that mindfulness has significant positive effects on individuals' physical health, cognitive, emotional and behavioral problems, and interpersonal adaptation. [14,15] Recent studies have confirmed that a mindfulness state can positively predict the achievement motivation at the workplace. [16,17] Focus on procrastination behavior among college students has been increasing in recent years.…”
Section: This Work Was Supported By the Humanities And Social Science...mentioning
confidence: 99%
“…Additionally, Jansen et al (2020) meta‐analysed eight RCTs of ACTp and reported moderate to strong effects for improving depression, acceptance and rehospitalisations rates. Most recently, Yip et al (2022) analysed five RCTs of ACTp and reported a significant moderately sized effect for reducing affective symptoms. However, the aforementioned meta‐analyses have not always found consistent effects on psychotic symptoms or other clinical outcomes, likely due to differences in their inclusion criteria and the particular studies analysed.…”
Section: Current Statusmentioning
confidence: 99%
“…Additionally, Jansen et al (2020) meta-analysed eight RCTs of ACTp and reported moderate to strong effects for improving depression, acceptance and rehospitalisations rates. Most recently,Yip et al (2022) analysed five RCTs of ACTp and reported a significant moderately sized effect for reducing affective symptoms. However, the T A B L E 2 Adjustments to ACT for people with psychosis.…”
mentioning
confidence: 99%